Defining Fire Safety Design in Architectural Education - Korkmaz, Ezgi (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
Fire safety design in buildings is a basic precaution for preserving security of life and property during fire. It should be addressed with care, since fire cannot be prevented completely and there is a risk of fire in any building. Building fire safety requires interdisciplinary study. However, it is especially important for architects to utilize their knowledge of the subject in professional education, as architects have a critical role in the design and construction processes of a building and must consider the law and regulations as design inputs. The fact that a fire safety design course is not offered as part of the curriculum of every architecture faculty, and that it is not being taught sufficiently within other course content, means there is a lack of awareness and knowledge. Many buildings in Turkey do not meet criteria for fire safety design, and this is considered a result of shortcomings in education. This study examined the curricula of 90 architecture departments in Turkey and a survey of academics was conducted. The results were evaluated and suggestions proposed accordingly.
Keywords: Architecture; architectural education; fire; fire safety design